A rare case of chronic traumatic diaphragmatic hernia requiring complex abdominal wall reconstruction. (2015) - Pakula, Andrea; Jones, Amber; Syed, Javed; Skinner, Ruby
Highlights: We present case of chronic traumatic diaphragmatic hernia. Traumatic diaphragmatic hernia are rare and under diagnosed. Chronic hernia may require complex abdominal reconstruction. Computed tomography has diagnostic characteristics. Abstract: Introduction: Traumatic diaphragmatic hernia is a rare and often under recognized complication of penetrating and blunt trauma. These injuries are often missed or there is a delay in diagnosis which can lead to enlargement of the defect and the development of abdominal or respiratory symptoms. Presentation of case: We report a case of an otherwise healthy 37 year old male who was involved in a motor vehicle accident at age twelve. He presented 25 years later with vague lower abdominal symptoms and was found to have a large chronic left sided diaphragmatic hernia involving the majority of his intra-abdominal contents. Repair of the defect with a biologic mesh was undertaken and the patient also required complex abdominal wall reconstruction due to loss of intra-abdominal domain from the chronicity of the hernia. A staged closure of the abdomen was performed first with placement of a Wittmann patch. Medical management of intra-abdominal hypertension was successful and the midline fascia was sequentially approximated at the bedside for three days. The final closure was performed with a component separation and implantation of a fenestrated biologic fetal bovine mesh to reinforce the closure. In addition, a lightweight Ultrapro mesh was placed for additional lateral reinforcement. The patient recovered well and was discharged home. Discussion: These injuries are rare and diagnosis is challenging. Mechanism and CT scan characteristics can aid clinicians. Conclusion: Blunt diaphragmatic injury is rare and remains a diagnostic challenge. Depending on the chronicity of the injury, repair may require complex surgical decision making.